The King and the Clown in South Indian Myth and Poetry - Shulman, David Dean, 1949- (Book collections on Project MUSE., 1985)
The author discusses the tragi-comic aspect of Chola kingship in relation to other Indian expressions of comedy, such as the Vidiisaka of Sanskrit drama, folk tales of the jester Tenali Rama, and clowns of the South Indian shadow-puppet theaters. The symbolism of the king emerges as part of a wider range of major symbolic figures--Brahmins, courtesans, and the tragic" bandits and warrior-heroes. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905